(untitled) (International Journal of Engineering and Computer Science, 2015)
TCP Congestion Control mechanisms needs an accurate loss differentiation scheme to improve the performance of TCP in wireless environment. This paper innovates a method to improve performance of TCP in mixed wired/wireless network by selecting one of the retransmission techniques, Selective Repeat (SR), Go Back N(GBN) depending on reason of losses and their rate of occurrence .The proposed approach exploits random losses to improve the throughput of TCP in mixed wired/wireless environment